Efficiency of Sudanese Banks: A Stochastic Frontier Approach (1996-2004) - Saber, Safiat Ali; Mahran, Hatim Ameer (Gezira Journal of Economic and Social Sciences, 2011)
Motivated by the catalytic role that the banking sector could play in the economy, this paper examined the efficiency of Sudanese banks under the intermediation and production approaches using the Stochastic Frontier method and panel data for 16 banks during the period 1996-2004. The results under both approaches indicate that Sudanese banks are inefficient. Nonetheless, specialized and joint venture banks are relatively less inefficient than commercial and government banks, respectively. Most important, although the majority of Sudanese banks operate under increasing returns to scale, these banks suffer from diseconomies of scale and have not yet exploited the advantages of increasing returns to scale as the very low estimates of overall average cost efficiency indicate. With an average efficiency score lower than the world's average, coupled with measures to open up the sector for foreign banks, Sudanese banks could survive fierce competition only by improving efficiency toward the world best practice frontiers. Efficiency could be improved through a number of measures, including the improvement of productivity through human capital development, the introduction of new technologies and internet banking services (involving automation and computerization) and, most important, through a credible management chosen on the basis of competence and expertise.